A review on the effect of bio-electrodes on denitrification and organic matter removal processes in bio-electrochemical systems - Mook, W.T.; Aroua, Mohamed Kheireddine; Chakrabarti, M.H.; Noor, I.M.; Irfan, M.F.; Low, C.T.J. (Elsevier, 2013)
The main factor that determines the success of a bio-electrochemical system (BES) is the bio-electrode. This paper reviews the direct as well as mediated electron transfer mechanisms in bio-electrodes. Some discussions on their influence upon the performance of microbial fuel and electrolysis cells are considered. Factors affecting organic matter removal at bioanodes and denitrification at biocathodes are elaborated upon. Important parameters for the successful simultaneous removal of contaminants are reported. The major conclusion from this work is that BES is able to remove organic matter and nitrates simultaneously from different wastewater samples at efficiencies greater than 90.